The Effect of Entrepreneurship Education on Increasing Nurse Entrepreneurs Interest in Nursing Students - Muhibbudin Muhibbudin; Mutia Sari (Jurnal Keperawatan Respati Yogyakarta, 2023)
The application of entrepreneurship education in higher education has become part of the core curriculum even in the health profession. One of the human resources who have a role or opportunity to become entrepreneurs in Indonesia is a nurse called a nursepreneur. Nurse is also a profession that has a great opportunity to become an entrepreneur in the health sector. The type of research used is correlative quantitative with a cross sectional design approach, The population in this study was 232 students. The sampling technique in this study used a simple technique of Random Sampling totaling 110 students. The results showed the correlation value (R) which is 0.390 and obtained the value of the coefficient of determination (R Square) of 0.152, this shows that there is an influence of entrepreneurial education variables to nursepreneur interest by 15.2%. Based on the signification value, a value of 0.04 < 0.05 was obtained so that it can be concluded that the influence between entrepreneurship education on increasing nursepreneur interest. Based on the t value, it is known that the calculated t value is 2,159 > table 1,985. It can be concluded that there is an influence between entrepreneurship education on increasing interest in nursing students